Overweight and poor? On the relationship between income and the body mass index - Dean Jolliffe (Institute for the Study of Labor (IZA), 2010)
Contrary to conventional wisdom, NHANES data indicate that the poor have never had a statistically significant higher prevalence of overweight status at any time in the last 35 years. Despite this empirical evidence, the view that the poor are less healthy in terms of excess accumulation of fat persists. This paper provides evidence that conventional wisdom is reflecting important differences in the relationship between income and the body mass index. The first finding is based on distribution-sensitive measures of overweight which indicates that the severity of overweight has been higher for the poor than the nonpoor throughout the last 35 years. The second finding is from a newly introduced estimator, unconditional quantile regression (UQR), which provides a measure of the income-gradient in BMI at different points on the unconditional BMI distribution. The UQR estimator indicates that the strongest relationship between income and BMI is observed at the tails of the distribution. There is a strong negative income gradient in BMI at the obesity threshold and some evidence of a positive gradient at the underweight threshold. Both of these UQR estimates imply that for those at the tails of the BMI distribution, increases in income are correlated with healthier BMI values.
Keywords: I1; I18; I32; 330; overweight; obesity; body mass index; unconditional quantile regression; Foster-Greer-Thorbecke poverty measures; NHANES